TINGKAT PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN SUMBER DAYA MANUSIA DI DESA CIPOTAKARI KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Nadila Norfazila Nurhayati; Andi Astinah Adnan; Erfina Erfina (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The study aims to determine the level of community participation in human resource development in Cipotakari Village, Panca Rijang District, Sidenreng Rappang Regency, and to identify the factors influencing community participation in human resource development. The research method used was quantitative with a descriptive approach. The study population consisted of 50 people, with a sample of 45 respondents determined using the Slovin formula with a 5% error rate. The sampling technique used was simple random sampling. Data collection techniques were carried out through observation, questionnaires, and literature study. The data analysis techniques used included descriptive statistical analysis, validity test, reliability test, and simple linear regression analysis with the assistance of SPSS and Likert Scale measurement. The results of the study showed that the recapitulation of the community participation variable reached 70.25%, which was categorized as “Good”. Meanwhile, the recapitulation of the human resource development variable reached 68.93%, also categorized as “Good”. The results of the simple linear regression analysis showed the equation Y = 4.604 + 0.573X with an R square value of 0.656, meaning that community participation had a positive influence of 65.6% on human resource development. The factors influencing community participation included age, gender, education, occupation and income, and length of residence.